2007
DOI: 10.1002/chin.200735182
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Plusbacin A3: Depsipeptide Antibiotic Active Against Vancomycin‐Resistant Bacteria.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Plusbacin A 3 has a structural motif commonly found in cyclic antimicrobial peptides: a cyclic-peptide core and a lipophilic side chain. 3 The cyclic core in plusbacin A 3 has eight amino acids cyclized through a lactone linkage between L-threo-β-hydroxyaspartic acid and a hydroxyl fatty acid subunit. The core is modified by attachment of an isotridecanyl side chain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plusbacin A 3 has a structural motif commonly found in cyclic antimicrobial peptides: a cyclic-peptide core and a lipophilic side chain. 3 The cyclic core in plusbacin A 3 has eight amino acids cyclized through a lactone linkage between L-threo-β-hydroxyaspartic acid and a hydroxyl fatty acid subunit. The core is modified by attachment of an isotridecanyl side chain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The activity of pb-A 3 is antagonized by the addition of cell-wall membrane particulates, and its inhibition of nascent peptidoglycan biosynthesis in a cell membrane extract suggests that pb-A 3 , like vancomycin, may target the peptidoglycan precursor lipid II. 2,3 Unlike vancomycin, however, pb-A 3 is active against VRE and its activity is not affected by the addition of the tripeptide acetyl-L-Lys-D-Ala-D-Ala. 2 Thus, it appears that the binding site utilized by pb-A 3 is distinct from that of vancomycin.…”
mentioning
confidence: 99%
“…xvi Sandoval et al, reported that (R)-3-hydroxy-n-phenylalkanoic acid had a significant antimicrobial effect against food pathogen such as Listeria monocytogenes present in the refrigerated food [33]. (R)-3-hydroxy-undecanoate is utilized for synthesis of depsipeptides (antibiotic/antifungal) [34]; lipid A mimic (immunobiological) [35]; (−)-tetrahydrolipstatin (antiobesity drug) [36]. (R)-3-hydroxyhexanoate is used for production of anti-microtubule agent such as analogs of laulimalide [37].…”
Section: Siv 231 Synthesis Of Chiral Compounds and Drugsmentioning
confidence: 99%